A systematic review and meta-analysis of adjuvant chemotherapy after chemoradiation for locally advanced cervical cancer. (April 2022) - Horeweg, Nanda; Mittal, Prachi; Gradowska, Patrycja L.; Boere, Ingrid; Nout, Remi A.; Chopra, Supriya
Abstract: We investigated whether the addition of adjuvant chemotherapy to chemoradiation improves overall survival (OS) and progression-free survival (PFS) by conducting a systematic review and meta-analysis. Systematic searches in the databases of PubMed, Embase and Web of Science yielded 881 articles. Two reviewer authors independently selected 31 articles for full text review and deemed eight studies eligible for inclusion. Two were randomised controlled trials (RCT), one was a large (n = 609) matched-case study and the remaining were small retrospective cohort studies; in total 2150 patients. Risk of bias assessment showed that the RCTs were at low risk and all other studies were at high risk of bias. Pooled hazard ratios for OS and PFS were 0.78 (95%CI 0.45–1.33, p = 0.36) and 0.85 (95%CI 0.65–1.10, p = 0.22), respectively. Analysis stratified by study design and sensitivity analysis showed similar results. Funnel plots showed significant publication bias due to a lack of small studies with negative outcomes. Highlights: First meta-analysis on adding adjuvant platinum-taxane chemotherapy to chemoradiation in cervical cancer including all RCTs. Independent systematic search, data extraction and risk assessment by 2 authors and thorough predefined statistical analysis. No benefit of adding platinum-taxane chemotherapy after chemoradiation for overall survival and progression-free survival. Publication bias on this topic is substantial, there is a lack of published small negative studies.